Bioactive sand filters for water treatment - Tan, Nicholas Shuo Jie (2017)
Bacteria and phosphate are two main contaminants in water and many means to remove these contaminants are available. This report aims to study the competitive adsorption of bacteria and phosphate onto iron oxyhydroxide(FeOOH)-coated surfaces. First, the performance of FeOOH-coated filters in removing bacteria and phosphate separately was examined through syringe column experiments. Following which, the effectiveness on an influent mixed with both water contaminants would be examined. Breakthrough curves of bacteria and phosphate were obtained. The FeOOH coating had generally increased the efficiencies of phosphate removal, though the impact on bacteria in this experiment is relatively uncertain. This may be attributed to the alteration of surface charge of the porous media by FeOOH, improving adsorption performance. In the presence of bacteria, phosphate removal by FeOOH was reduced. This study indicates that there may be competitive adsorption between phosphate and bacteria to FeOOH surfaces.